2000
DOI: 10.1002/(sici)1526-4998(200001)56:1<74::aid-ps96>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring resistance to diflubenzuron and deltamethrin in French codling moth populations (Cydia pomonella)

Abstract: French populations of codling moth have developed resistance to several insecticide classes. The susceptibility of susceptible and resistant laboratory strains to diflubenzuron and deltamethrin was evaluated using different exposure methods against various life stages. The tarsal contact method for adults was found to be an appropriate method for testing neurotoxic compounds such as deltamethrin. Insect growth inhibitors, like diflubenzuron, need to be analysed on juvenile instars. Monitoring methodologies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 21 publications
1
87
2
3
Order By: Relevance
“…Larger body size is related to higher detoxification capacity, which confers resistance towards insecticides (Reyes et al, 2004(Reyes et al, , 2015Fuentes-Contreras et al, 2007). Therefore, females with larger body size have higher levels of insecticide resistance than do males with a smaller body size (Varela et al, 1993;Sauphanor et al, 2000;Reyes et al, 2004Reyes et al, , 2015Fuentes-Contreras et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Larger body size is related to higher detoxification capacity, which confers resistance towards insecticides (Reyes et al, 2004(Reyes et al, , 2015Fuentes-Contreras et al, 2007). Therefore, females with larger body size have higher levels of insecticide resistance than do males with a smaller body size (Varela et al, 1993;Sauphanor et al, 2000;Reyes et al, 2004Reyes et al, , 2015Fuentes-Contreras et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Some studies in codling moth have found an association between insecticide resistance, body size, and sexual dimorphism because females have higher levels of resistance compared with males, which usually are of smaller body size (Varela et al, 1993;Sauphanor et al, 2000;Reyes et al, 2004Reyes et al, , 2015Fuentes-Contreras et al, 2007). Body size has also been related to dispersal capability in the codling moth: in the same population, larger females tend to be more fecund, live longer, and disperse less than smaller females (Gu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Lenormand and Raymond (1998) described a management model leading to the confinement of the resistance genes, by the use of fluctuating intensities of both gene flow and selection (for and against resistance). In south-eastern France apple orchards, the mean frequency of resistance was close to 75% according to recent field collections (Sauphanor et al, 2000). Given that two generations per year can successfully reproduce in this region, the present study suggested that more than 5 years of relaxation of diflubenzuron spraying would be required in order to result in an agronomically effective reversion of resistance in C. pomonella populations.…”
Section: Pleiotropic Costs and Resistance Managementmentioning
confidence: 99%
“…Diflubenzuron is also registered to treat grasslands infested with grasshoppers -which often devastate nearby crops -providing an important replacement for OP and carbamate insecticides. Resistance to diflubenzuron in codling moth populations occurs in France (Sauphanor et al 2000), indicating the need for the careful rotation of this insecticide with insecticides that have different modes of action.…”
Section: Liriomyza Leafminer Adultmentioning
confidence: 99%